A boldly comparative approach will strengthen co-evolutionary accounts of musicality's origins. (30th September 2021) - Rendell, Luke; Doolittle, Emily L.; Garland, Ellen C.; South, Alex
Abstract: Focus on the evolutionary origins of musicality has been neglected relative to attention on language, so these new proposals are welcome stimulants. We argue for a broad comparative approach to understanding how the elements of musicality evolved, and against the use of overly simplistic evolutionary accounts.